1991
DOI: 10.1002/ajh.2830370316
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary report on the use of desferrioxamine in the treatment of Plasmodium falciparum malaria

Abstract: The administration of 0.5 g (IM) of desferrioxamine every 12 hr for 3 days with 25 mg/kg (total dose for three days) of chloroquine abated the parasitemia of Plasmodium falciparum infected individuals more rapidly than chloroquine alone. Two patients with in vitro evidence of total or partial resistance to chloroquine also were successfully treated with the combination of drugs, and were free of parasitized red cells by day 7. Further clinical trials and development of desferrioxamine in the treatment of P. fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…The suggestion that iron chelation might represent a useful approach to antimicrobial therapy is not new (13,41,42), yet only recently has it been intensively investigated, most successfully in malaria research (16,19,40). The current work confirms previous observations that iron chelation with DFO inhibits the growth of P. carinii in vitro (46) and in vivo (11), and also demonstrates that alterations in ultrastructure parallel the inhibitory effect.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The suggestion that iron chelation might represent a useful approach to antimicrobial therapy is not new (13,41,42), yet only recently has it been intensively investigated, most successfully in malaria research (16,19,40). The current work confirms previous observations that iron chelation with DFO inhibits the growth of P. carinii in vitro (46) and in vivo (11), and also demonstrates that alterations in ultrastructure parallel the inhibitory effect.…”
Section: Discussionsupporting
confidence: 80%
“…It has been suggested, therefore, that manipulation of iron availability be exploited as a therapeutic tool (13,41,42). In fact, several iron chelators, among them deferoxamine (DFO), demonstrate antimalarial activity in cell culture and animal models (14,33,47,48), and recently, iron chelation with DFO has been shown to be an effective adjunct to traditional antimalarial therapy in asymptomatic parasitemic adults and children with cerebral malaria (16,19,40).Clarkson et al (11) examined the effects of DFO on the progression of reactivated latent P. carinii pneumonia in rats and showed that DFO therapy reduces the lung cyst count in a dose-dependent manner. A subsequent preliminary study from the laboratory of Weinberg and Shaw (46) showed that DFO suppresses the growth of P. carinii in an established cell culture model at concentrations safely achievable in human serum.…”
mentioning
confidence: 99%
“…This truism also applies to iron chelators, which have already scored success in the management of various diseases ( 1 ), including malaria (9). To gain knowledge on the mode of action of iron chelators as antimalarial agents and to determine the basis for their specific effects on infected cells it is necessary to delineate the routes by which they permeate into cells and to identify the critical iron pools.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that DFO congeners display effective antimalarial activity both in vitro (2)(3)(4)(5) and in vivo (4,(6)(7)(8)(9), but as with many other drugs, their mode of action has remained elusive (1). The information available indicates that DFO acts without affecting serum (4,10) or normal red cell iron pools (3,10), that it gains a restricted access to infected cells ( 11 ), and that its antimalarial action is manifested only in the advanced stages of parasite development and only after prolonged exposure of cells to drug (3,12).…”
mentioning
confidence: 99%
“…Studies in human malaria showed that DFO alone, or in combination with standard therapy, enhances parasite clearance in asymptomatic and severe malaria (Traore et al, 1991;Gordeuk et al, 1992;Mabeza et al, 1996). Continuous infusion of DFO over a 3 day period is required to obtain enhanced parasite clearance in human malaria (Mabeza et al, 1996).…”
Section: Discussionmentioning
confidence: 99%